Prehabilitation for patients with colorectal cancer: a snapshot of current daily practice in Dutch hospitals - Charlotte J. L. Molenaar; Muriël Reudink; Charissa R. Sabajo; Loes Janssen; Rudi M. H. Roumen; Joost M. Klaase; Gerrit D. Slooter (Perioperative Medicine, 2023)
Abstract Background Multimodal prehabilitation programmes are increasingly being imbedded in colorectal cancer (CRC) pathways to enhance the patient’s recovery after surgery. However, there is no (inter)national consensus on the content or design of such a programme. This study aimed to evaluate the current practice and opinion regarding preoperative screening and prehabilitation for patients undergoing surgery for CRC throughout the Netherlands. Methods All regular Dutch hospitals offering colorectal cancer surgery were included. An online survey was sent to one representative colorectal surgeon per hospital. Descriptive statistics were used for analyses. Results Response rate was 100% (n = 69). Routine preoperative screening of patients with CRC for frailty, diminished nutritional status and anaemia was the standard of care in nearly all Dutch hospitals (97%, 93% and 94%, respectively). Some form of prehabilitation was provided in 46 hospitals (67%) of which more than 80% addressed nutritional status, frailty, physical status and anaemia. All but two of the remaining hospitals were willing to adopt prehabilitation. The majority of the hospitals offered prehabilitation to specific subgroups of patients with CRC, such as the elderly (41%), the frail (71%) or high-risk patients (57%). There was high variability in the setting, design and content of the prehabilitation programmes. Conclusions Whereas preoperative screening is sufficiently incorporated in Dutch hospitals, standardised enhancement of the patient’s condition in the context of multimodal prehabilitation seems to be challenging. This study presents an overview of current clinical practice in the Netherlands. Uniform clinical prehabilitation guidelines are vital to diminish heterogeneity in programmes and to produce useful data to enable a nationwide implementation of an evidence-based prehabilitation programme.